PENGARUH EDUKASI IBU PEDULI DM TERHADAP PENGETAHUAN DAN PERILAKU PENCEGAHAN DM - Hanifah Maharani; Yoga Adhi Dana; Cyntia Ratna Sari (FLORONA : Jurnal Ilmiah Kesehatan, 2022)
This study aims to find out the influence of education of DM-concerned mothers on changes in knowledge and behavior of DM prevention. Quacy experimental study using the pre-test post-test design with control group. The study took the maternal population in Japanese villages, with purposive sampling techniques. Bivariate analysis tested differences in average results and changes in knowledge, as well as maternal behavior before and after intervention in one group tested with paired t-tests while between groups using independent ttest . The correlation test with Pearson and Rank spearman, while the effect size to see the effect. Paired ttest showed there are significant differences in knowledge and behavior before and after education in the intervention group (p<0.05). The Independent ttest showed there were differences in knowledge and behavior changes in the control and intervention groups (p<0.05). Test results (effect sizes 0.8 and 0.9) show DM education has an effect on changes in knowledge and preventive behavior. Changes in knowledge and behavior in the intervention group were higher than in the control group. The education provided has a strong influence on changes in maternal knowledge and behavior about dm prevention.